Analysis of miRNAs in Two Wheat Cultivars Infected With Puccinia striiformis f. sp. tritici - Ramachandran, Sowmya R.; Mueth, Nicholas A.; Zheng, Ping; Hulbert, Scot H. (Frontiers in Plant Science, 2020)
MicroRNAs are small RNAs that regulate gene expression in eukaryotes. In this study, we analyzed the small RNA profiles of two cultivars that exhibit different reactions to stripe rust infection: one susceptible, the other moderately resistant. Using small RNA libraries prepared from the two wheat cultivars infected with stripe rust fungus (Puccinia striiformis), we identified 182 previously-known miRNAs, 91 variants of known miRNAs, and 163 candidate novel wheat miRNAs. Known miRNA loci were usually copied in all three wheat sub-genomes, whereas novel miRNA loci were often specific to a single sub-genome. DESeq2 analysis of differentially expressed microRNAs revealed 23 microRNAs that exhibit cultivar-specific differences. TA078/miR399b showed cultivar-specific differential regulation in response to infection. Using different target prediction algorithms, 145 miRNAs were predicted to target wheat genes, while 69 miRNAs were predicted to target fungal genes. We also confirmed reciprocal expression of TA078/miR399b and MIR9664 and their target genes in different treatments, providing evidence for miRNA-mediated regulation during infection. Both known and novel miRNAs were predicted to target fungal genes, suggesting trans-kingdom regulation of gene expression. Overall, this study contributes to the current repository of wheat miRNAs and provides novel information on the yet-uncharacterized roles for miRNAs in the wheat-stripe rust pathosystem.